Transthyretin is not necessary for thyroid hormone metabolism in conditions of increased hormone demand - Sousa, João Carlos (2005)
Thyroid hormones circulate in blood mainly bound to plasma proteins. Transthyretin is the major thyroxine plasma carrier in mice. Studies in transthyretin-null mice revealed that the absence of transthyretin results in euthyroid hypothyroxinemia and normal thyroid hormone tissue distribution, with the exception of the choroid plexus in the brain. Therefore, transthyretin does not influence normal thyroid hormone homeostasis under standard laboratory conditions. To investigate if transthyretin has a buffer/storage role we challenged transthyretin-null and wild-type mice with conditions of increased hormone demand: (i) exposure to cold, which elicits thermogenesis, a process that requires thyroid hormones; and (ii) thyroidectomy, which abolishes thyroid hormone synthesis and secretion and induces severe hypothyroidism. Transthyretin-null mice responded as the wild-type both to changes induced by stressful events, namely in body weight, food intake and thyroid hormone tissue content, and in the mRNA levels of genes whose expression is altered in such conditions. These results clearly exclude a role for transthyretin in thyroid hormone homeostasis even under conditions of increased hormone demand.